Hollow core anti-resonance optical fiber and preparation method thereof, optical fiber cable
By designing the hollow core anti-resonant optical fiber made of 27As2Te2-39GeSe2-34As2Se3 glass material, the problem of missing optical transmission materials in the 12μm~30μm band is solved, and low-loss optical transmission is achieved, filling the technical gap in this band.
Patent Information
- Application Number
- CN202510213264.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-26
AI Technical Summary
The prior art is difficult to achieve low loss optical transmission in the 12μm~30μm band, resulting in the lack of optical transmission materials in this band.
An air-core anti-resonant fiber is used, which is made of 27As2Te2-39GeSe2-34As2Se3 glass material, including an outer tube and an equally arranged capillary tube to form an air core. Low-loss optical transmission is achieved by rationally designing fiber structural parameters such as the number of capillaries, air core diameter, capillary outer diameter, wall thickness and spacing.
A low-loss transmission window with a theoretical transmission loss of less than 2dB/m is realized in the 12μm~30μm band, filling the gap in optical transmission materials in this band, and achieving efficient far-infrared terahertz critical band transmission.
Smart Images

Figure CN119717122B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of optical technology, and in particular to a hollow-core anti-resonant optical fiber and a preparation method thereof, and an optical fiber cable. Background Art
[0002] As a one-dimensional light transmission tool, the biggest feature of glass optical fiber is that it can be used to achieve flexible transmission of optical signals. It is a very important basic optical tool and the material basis for building various optical systems.
[0003] The transmission window of glass fiber is restricted by the phonon energy of its material. Therefore, glass fibers made of different materials can achieve different infrared transmission limits. Among the various types of glass fibers reported so far, the phonon energy of quartz glass fiber is relatively high, so that its infrared transmission limit is only 2.4μm (micrometer); the infrared transmission limits of heavy metal oxide glass fiber represented by tellurite glass fiber and fluoride glass fiber can reach 5μm and 6μm respectively; Te (tellurium)-based glass in chalcogenide glass has the lowest phonon energy, and the infrared transmission limit of Te-based glass fiber can reach 12μm.
[0004] However, glass optical fibers that can efficiently transmit the 12μm~30μm band have not yet been reported. Specifically, the 12~30μm band is a critical spectral band between the far-infrared spectrum and the terahertz spectrum, and is the critical region for the transition from macroscopic electronics to microscopic photonics. It covers the characteristic fingerprint spectra of many molecules, the energy band spectra of materials, and the radiation spectra of cosmic space. Its special spectral position makes the 12μm~30μm band have important applications in biological detection, cancer diagnosis, characteristic spectral imaging, semiconductor material analysis, cosmological research and other fields.
[0005] Therefore, in order to meet the communication needs in the 12μm~30μm band, there is an urgent need for a new type of optical fiber that can achieve low-loss transmission in the 12μm~30μm band. Summary of the invention
[0006] The purpose of the embodiments of the present application is to provide a hollow core anti-resonant optical fiber and a preparation method thereof, and an optical fiber cable, so as to solve the problem of lack of optical transmission materials in the 12μm~30μm band. The specific technical solution is as follows:
[0007] In a first aspect, the present application provides a hollow core antiresonant optical fiber, comprising:
[0008] External pipe;
[0009] A plurality of capillaries are arranged on the inner wall of the outer tube at equal intervals along the extension direction of the outer tube;
[0010] An air core, formed by being surrounded by the plurality of capillaries;
[0011] Wherein, the material of the outer tube and the capillary is 27As2Te2-39GeSe2-34As2Se3 glass.
[0012] In one embodiment of the present application, the number of the capillaries is 8, the diameter of the air core is between 420 μm and 440 μm, the outer diameter of the capillary is between 160 μm and 180 μm, the wall thickness of the capillary is between 13 μm and 17 μm, and the interval between the capillaries is between 57 μm and 63 μm;
[0013] The diameter of the air core is the diameter of the inscribed circle formed by the capillaries, and the interval between the capillaries is the minimum distance between adjacent capillaries.
[0014] In one embodiment of the present application, the hollow-core antiresonant optical fiber has a low-loss transmission window in the 12 μm-30 μm band with a theoretical transmission loss lower than 2 dB / m.
[0015] In a second aspect, the present application provides a method for preparing a hollow core antiresonant optical fiber, comprising:
[0016] Elemental As, elemental Te, elemental Ge and elemental Se were weighed in a molar ratio of 122:54:39:146, and 27As2Te2-39GeSe2-34As2Se3 glass was prepared by melting and annealing.
[0017] Prepare a glass mother tube using the 27As2Te2-39GeSe2-34As2Se3 glass;
[0018] Performing wire drawing on the glass mother tube to obtain a capillary tube;
[0019] Inserting a plurality of the capillaries into a glass mother tube, and arranging the inserted capillaries at equal intervals on the inner wall of the glass mother tube to obtain an optical fiber preform;
[0020] The optical fiber preform is subjected to a drawing process to obtain a hollow-core anti-resonant optical fiber.
[0021] In one embodiment of the present application, the process of preparing 27As2Te2-39GeSe2-34As2Se3 glass by melting and annealing includes:
[0022] Adding the single substance Ge and the single substance Te into a melting container, placing the melting container into a melting furnace, melting the single substance Ge and the single substance Te, and obtaining an alloy after cooling;
[0023] The single element As and the single element Se are added into the melting container, and the melting container is placed into a melting furnace to melt the alloy, the single element As and the single element Se, and the molten glass obtained by the melting is quenched and then annealed to obtain 27As2Te2-39GeSe2-34As2Se3 glass.
[0024] In one embodiment of the present application, when the elemental Ge and the elemental Te are melted, the melting temperature is between 850°C and 900°C, and the melting time is between 5 hours and 10 hours; when the alloy, the elemental As and the elemental Se are melted, the melting temperature is between 750°C and 800°C, and the melting time is more than 10 hours.
[0025] In one embodiment of the present application, the number of capillaries inserted into the glass mother tube is 8, and in the hollow-core antiresonant optical fiber, the diameter of the air core is between 420 μm and 440 μm, the outer diameter of the capillary is between 160 μm and 180 μm, the wall thickness of the capillary is between 13 μm and 17 μm, and the spacing between the capillaries is between 57 μm and 63 μm; wherein, the diameter of the air core is the diameter of the inscribed circle formed by each of the capillaries, and the spacing between the capillaries is the minimum distance between adjacent capillaries.
[0026] In one embodiment of the present application, during the drawing process of the optical fiber preform, each capillary in the optical fiber preform is connected to a first controlled air pressure, and the air core formed by the capillaries is connected to a second controlled air pressure, and the first controlled air pressure is 5 kPa to 20 kPa higher than the second controlled air pressure.
[0027] In one embodiment of the present application, during the drawing process of the glass mother tube, the glass mother tube is in an inert gas; during the drawing process of the optical fiber preform, the optical fiber preform is in an inert gas.
[0028] In a third aspect, the present application provides an optical fiber cable, comprising at least one hollow-core antiresonant optical fiber as described in any one of the first aspects.
[0029] Beneficial effects of this application:
[0030] The hollow-core anti-resonant optical fiber and its preparation method and optical fiber cable provided by the present application include an outer tube and a plurality of capillaries arranged at equal intervals on the inner wall of the outer tube, and the plurality of capillaries surround an air core, wherein the outer tube and the capillaries are made of 27As2Te2-39GeSe2-34As2Se3 glass. Theoretical calculation results show that the hollow-core anti-resonant optical fiber provided by the present application has a low-loss transmission window with a theoretical transmission loss of less than 2dB / m in the 12μm~30μm band, and can achieve efficient transmission in the 12μm~30μm far-infrared terahertz critical band.
[0031] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0033] Figure 1 A schematic diagram of the structure of a hollow-core anti-resonant optical fiber provided in an embodiment of the present application;
[0034] Figure 2 Thermal test curve of 27As2Te2-39GeSe2-34As2Se3 glass provided in the embodiment of the present application;
[0035] Figure 3 The infrared transmission spectrum of the 27As2Te2-39GeSe2-34As2Se3 glass provided in the embodiment of the present application;
[0036] Figure 4 The refractive index dispersion curve of the 27As2Te2-39GeSe2-34As2Se3 glass provided in the embodiment of the present application;
[0037] Figure 5 The theoretical loss spectrum of the hollow-core antiresonant optical fiber provided in Example 2-1 of the present application;
[0038] Figure 6 The theoretical loss spectrum of the hollow-core antiresonant optical fiber provided in Example 2-2 of the present application;
[0039] Figure 7 The theoretical loss spectrum of the hollow-core antiresonant optical fiber provided in Examples 2-3 of the present application;
[0040] Figure 8This is a micrograph of the end face of the hollow-core antiresonant optical fiber prepared in Example 3-1 of the present application;
[0041] Fig. 9 This is the measured loss spectrum of the hollow-core antiresonant optical fiber provided in Experimental Example 3-1 of the present application. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0043] In order to solve the problem of lack of optical fiber transmission materials in the 12μm~30μm band, the present application provides a hollow core anti-resonant optical fiber, such as Figure 1 As shown, the hollow core antiresonant optical fiber comprises:
[0044] Outer tube 1;
[0045] A plurality of capillaries 2 are arranged on the inner wall of the outer tube 1 at equal intervals along the extension direction of the outer tube 1;
[0046] An air core 3 is formed by being surrounded by the plurality of capillaries 2;
[0047] The outer tube 1 and the capillary tube 2 are made of 27As2Te2-39GeSe2-34As2Se3 glass.
[0048] In the above-mentioned hollow-core anti-resonant optical fiber, each capillary tube 2 disposed on the inner wall of the outer tube 1 constitutes an optical cladding, surrounding an air core 3 in the hollow-core anti-resonant optical fiber, and the air core 3 constitutes the main light-guiding region in the optical fiber. Exemplarily, the number of capillaries 2 in the hollow-core anti-resonant optical fiber can be set to 4, 6, 8, etc.
[0049] Compared with the traditional core-clad structure optical fiber, the biggest feature of the hollow-core anti-resonant optical fiber of this structure is that the overlap coefficient between the core mode field and the cladding material mode field is very low, so that the light intensity in the optical fiber is mainly confined in the air core 3, so that the absorption loss of the cladding material significantly reduces the impact of the optical fiber transmission loss, thereby helping to expand the transmission window of the optical fiber (in the field of optical fiber communication, the transmission window refers to a wavelength range where the optical fiber transmission loss is very small). In addition, in the above-mentioned hollow-core anti-resonant optical fiber, there is no contact point between the capillaries 2, but they are spaced apart from each other, eliminating the resonance points around the air core 3, helping to reduce the mode coupling between the air core 3 and the optical cladding, and further reducing the transmission loss.
[0050] For the above-mentioned hollow core anti-resonant optical fiber, the main optical fiber structural parameters that affect the optical fiber transmission loss include: the number of capillaries 2, the diameter of the air core 3, the wall thickness of the capillaries 2, and the interval between the capillaries 2. In order to ensure the optical fiber performance of the hollow core anti-resonant optical fiber, the present application has made specific designs for these parameters:
[0051] In one embodiment of the present application, the number of capillaries 2 in the hollow-core antiresonant optical fiber is 8, and the diameter D of the air core 3 is between 420μm and 440μm, for example, 420μm, 430μm, and 440μm; the outer diameter d of the capillary 2 is between 160μm and 180μm, for example, 160μm, 170μm, and 180μm; the wall thickness f of the capillary 2 is between 13μm and 17μm, for example, 13μm, 14μm, 15μm, 16μm, and 17μm; the interval g between the capillaries 2 is between 57μm and 63μm, for example, 57μm, 58μm, 59μm, 60μm, 61μm, 62μm, and 63μm.
[0052] Specifically, the outer tube 1 , the capillary tube 2 and the air core 3 are all in the shape of a perfect circle.
[0053] like Figure 1 As shown, the diameter D of the air core 3 specifically refers to the diameter of the inscribed circle surrounded by each capillary 2 , and the interval g between the capillaries 2 specifically refers to the minimum distance between adjacent capillaries 2 .
[0054] By setting the fiber structure parameters of the hollow-core antiresonant fiber within the above-given range, it is beneficial for the hollow-core antiresonant fiber to achieve good optical transmission performance in the 12μm~30μm band. Theoretical calculation results show that when the structural parameters of the hollow-core antiresonant fiber are within the above-given range, the hollow-core antiresonant fiber has a low-loss transmission window in the 12μm~30μm band with a theoretical transmission loss lower than 2dB / m, filling the gap of low-loss transmission fiber in the 12μm~30μm band. The specific theoretical calculation and corresponding experimental test results will be given later.
[0055] In addition, the outer diameter of the outer tube 1 in the hollow-core anti-resonant optical fiber will not have a significant impact on the optical transmission performance of the hollow-core anti-resonant optical fiber, but is mainly used to provide a supporting effect for each capillary 2. Therefore, it can be set according to actual needs, and the present application does not impose specific restrictions on its size.
[0056] Corresponding to the above-mentioned hollow-core antiresonant optical fiber, the present application also provides a method for preparing a hollow-core antiresonant optical fiber, comprising the following steps:
[0057] Step S1: weigh As, Te, Ge and Se according to the composition ratio of the components in 27As2Te2-39GeSe2-34As2Se3 glass, and prepare 27As2Te2-39GeSe2-34As2Se3 glass by melting and annealing.
[0058] Step S2: Prepare a glass mother tube using 27As2Te2-39GeSe2-34As2Se3 glass.
[0059] Step S3: performing wire drawing on the glass mother tube to obtain a capillary tube.
[0060] Step S4: inserting a plurality of capillaries into a glass mother tube, and arranging the inserted capillaries at equal intervals on the inner wall of the glass mother tube to obtain an optical fiber preform.
[0061] Step S5: Drawing the optical fiber preform to obtain a hollow-core antiresonant optical fiber.
[0062] In the above step S1, the ratio of elemental As, elemental Te, elemental Ge and elemental Se is determined specifically according to the components of the 27As2Te2-39GeSe2-34As2Se3 glass. In the present application, the molar ratio of As, Te, Ge and Se is 122:54:39:146. Then, elemental As, elemental Te, elemental Ge and elemental Se are weighed according to the determined ratio, and then the weighed elements are used to prepare the 27As2Te2-39GeSe2-34As2Se3 glass by melting and annealing. The melting and annealing method specifically refers to: heating the raw materials so that the elemental raw materials are mixed and reacted with each other to form a glass liquid, and then the glass liquid is quenched and annealed to form a solid glass.
[0063] In one example, high-purity single elements As, Te, Ge and Se with a purity of not less than 99.99% are used as raw materials for preparing 27As2Te2-39GeSe2-34As2Se3 glass.
[0064] In the above steps S2 to S4, specifically, according to the number n of capillaries contained in the designed hollow-core antiresonant optical fiber, a plurality of glass mother tubes can be prepared using 27As2Te2-39GeSe2-34As2Se3 glass, and n capillaries can be prepared by drawing some of the glass mother tubes, and the n capillaries are inserted into another glass mother tube, and the inserted capillaries are arranged at equal intervals on the inner wall of the glass mother tube to obtain an optical fiber preform. For example, if the designed hollow-core antiresonant optical fiber contains 8 capillaries, a total of 8 capillaries need to be prepared by drawing the glass mother tube, and the 8 capillaries are inserted into another glass mother tube, and the 8 capillaries are arranged at equal intervals on the inner wall of the glass mother tube to obtain an optical fiber preform.
[0065] In practical applications, the glass mother tube can be prepared by rotating tube making, punching tube making, or extruding tube making, and the present application does not limit the specific tube making method. In addition, after the glass mother tube is subjected to wire drawing to obtain the capillary tube, the capillary tube can be shortened to the same length as the glass mother tube, and then n shortened capillaries are inserted into the glass mother tube. After the n capillaries are arranged at equal intervals on the inner wall of the glass mother tube, the two ends of the n capillaries are fixed to the glass mother tube to obtain a glass preform.
[0066] In one example, a glass mother tube can be drawn by an infrared fiber drawing tower.
[0067] In the above-mentioned step S5, by drawing the optical fiber preform so that the drawn optical fiber preform meets the preset target structural parameters, such as the preset air core diameter range, capillary outer diameter range, capillary wall thickness range, capillary spacing range, etc., a hollow-core antiresonant optical fiber can be obtained.
[0068] In one example, an optical fiber preform can be drawn by an infrared optical fiber drawing tower.
[0069] In one embodiment of the present application, during the process of drawing the glass mother tube in the above step S3 and during the process of drawing the optical fiber preform in the above step S5, the drawing temperature used is 315°C to 320°C.
[0070] In one embodiment of the present application, the optical fiber structural parameters of the hollow-core antiresonant optical fiber prepared by the above-mentioned steps S1 to S5 satisfy the following requirements: the number of capillaries in the hollow-core antiresonant optical fiber is 8, the diameter of the air core is between 420 μm and 440 μm, the outer diameter of the capillary is between 160 μm and 180 μm, the wall thickness of the capillary is between 13 μm and 17 μm, and the spacing between the capillaries is between 57 μm and 63 μm.
[0071] In one embodiment of the present application, in the above step S1, after weighing the elemental As, elemental Te, elemental Ge and elemental Se according to the composition content ratio, the 27As2Te2-39GeSe2-34As2Se3 glass is prepared by the following steps:
[0072] Step S11: adding single element Ge and single element Te into a melting container, placing the melting container into a melting furnace, melting the single element Ge and single element Te, and obtaining an alloy after cooling;
[0073] Step S12: Add elemental As and elemental Se into a melting container, and place the melting container into a melting furnace to melt the alloy, elemental As and elemental Se, quench the melted glass liquid, and then anneal it to obtain 27As2Te2-39GeSe2-34As2Se3 glass.
[0074] In the actual glass preparation process, the melting container is usually a quartz tube, and the melting furnace is usually a swing furnace. If glass is prepared according to the conventional chalcogenide glass preparation process, the single substances of various raw materials required for glass preparation are usually added into the quartz tube at one time, and the quartz tube is placed in the swing furnace, and the quartz tube is heated by the swing furnace to melt the raw materials, and then the melted glass liquid is quenched and annealed to obtain glass.
[0075] However, for the 27As2Te2-39GeSe2-34As2Se3 glass used in this application, one point that needs to be noted in the process flow of glass preparation is that the melting point of the single substance Ge as the preparation raw material is very high (melting point is 937.4°C), resulting in the need to use a very high melting temperature (generally set to 900°C) to achieve glass preparation when the conventional chalcogenide glass preparation process mentioned above is commonly used. As as a raw material will corrode the quartz tube under high temperature conditions (above 750°C), forming byproducts such as SiO2 microparticles and oxygen impurities, thereby introducing impurities into the finished 27As2Te2-39GeSe2-34As2Se3 glass, which may cause the optical performance of the hollow core anti-resonance optical fiber prepared using the 27As2Te2-39GeSe2-34As2Se3 glass to be lost, resulting in an increase in the transmission loss of the hollow core anti-resonance optical fiber.
[0076] In order to avoid the corrosion of As on the quartz tube under high temperature conditions as much as possible and reduce the introduction of impurities in 27As2Te2-39GeSe2-34As2Se3 glass, the present application provides a low-temperature synthesis preparation technology for Ge-containing chalcogenide glass, which adopts two melting processes in steps to prepare 27As2Te2-39GeSe2-34As2Se3 glass, namely: firstly, the single element Ge and the single element Te (melting point is 449.5°C) are subjected to a first melting treatment, and an alloy is obtained after cooling, and then the alloy is subjected to a second melting treatment with single elements As (melting point is 817°C) and single element Se (melting point is 221°C), and the melted glass liquid is quenched and annealed to obtain 27As2Te2-39GeSe2-34As2Se3 glass.
[0077] Based on the description in the foregoing, it is easy to understand that elemental Ge is the raw material with the highest melting point among the raw materials required to prepare 27As2Te2-39GeSe2-34As2Se3 glass, and has an important influence on the melting temperature required to be achieved in the melting process. What those skilled in the art can understand is that after the elemental Ge with a higher melting point forms an alloy with the elemental Te with a lower melting point, the melting point of the alloy is lower than the melting point of elemental Ge. Therefore, the present application prepares elemental Ge and elemental Te into an alloy with a melting point lower than that of elemental Ge, and then adds elemental As and elemental Se to the alloy for a second melting treatment. The melting temperature required for the second melting treatment is lower than the melting temperature required for a one-time melting treatment of elemental As, elemental Te, elemental Ge and elemental Se according to a conventional preparation process. Therefore, compared with the conventional chalcogenide glass preparation process, when preparing 27As2Te2-39GeSe2-34As2Se3 glass according to the above steps S11-S12 provided in the present application, As will participate in the melting process at a lower temperature, which will help reduce the degree of As corrosion on the quartz tube and reduce the introduction of impurities in the finished 27As2Te2-39GeSe2-34As2Se3 glass, thereby ensuring the optical performance of the hollow-core antiresonant optical fiber subsequently prepared by the 27As2Te2-39GeSe2-34As2Se3 glass.
[0078] In one embodiment of the present application, when performing the melting treatment of elemental Ge and elemental Te, the melting temperature is between 850°C and 900°C, for example, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C; the melting treatment time is between 5 hours and 10 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours; the heating rate to the melting temperature does not exceed 3°C / minute, for example, it can be 2°C / minute, 2.5°C / minute, 3°C / minute.
[0079] When melting the alloy formed by elemental Ge and elemental Te, and elemental As and elemental Se, the melting temperature is between 750°C and 800°C, for example, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C; the melting treatment time is more than 10 hours, for example, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours; the heating rate to the melting temperature does not exceed 3°C / minute, for example, it can be 2°C / minute, 2.5°C / minute, 3°C / minute.
[0080] The melting treatment time can be understood as the time for which the quartz tube is kept at the melting temperature after the temperature of the quartz tube is raised to the melting temperature.
[0081] According to the Ge 30 As 10 Se 30 Te 30 Taking the preparation process of glass optical fiber as an example (Optical Fiber and Cable and Its Application Technology, 1995, 3, 54-58), the composition elements contained in this glass are consistent with the composition elements contained in the 27As2Te2-39GeSe2-34As2Se3 glass provided in this application, and in this Ge 30 As 10 Se 30 Te 30 In the preparation process of glass optical fiber, the weighed single elements As, Te, Ge and Se are placed in a quartz tube at one time, melted at 900°C, and Ge is obtained after cooling and annealing. 30 As 10 Se 30 Te 30 Compared with the glass preparation process under this traditional method, the present application reduces the melting temperature of the melting process in which As participates to between 750°C and 800°C by first preparing an alloy of Ge and Te, and then melting the alloy, As and Se. This can significantly reduce the degree of As corrosion on the quartz tube and reduce the introduction of impurities into the finished glass.
[0082] In addition, with respect to the above-mentioned step S5, since a tensile force needs to be applied to both ends of the optical fiber preform during the drawing process of the optical fiber preform, the glass mother tube and the capillaries arranged in the glass mother tube may shrink due to the influence of surface tension, resulting in a change in their geometric shape (for example, the cross-sectional shape changes from a perfect circular surface to an elliptical surface). In one embodiment of the present application, in order to eliminate the influence of the surface tension on the glass mother tube and the capillaries in the optical fiber preform, a controlled air pressure is connected to each capillary in the optical fiber preform and the air core formed by each capillary to maintain the geometric shape of the glass mother tube and each capillary.
[0083] Specifically, since the size of the capillary provided in the glass mother tube is smaller than that of the glass mother tube, the capillary is more affected by the surface tension. Therefore, in order to avoid the shrinkage of the capillary under the action of surface tension, it is necessary to apply a larger control air pressure to the capillary than to the air core, so as to effectively control the geometric shape of the capillary. In the present application, each capillary in the optical fiber preform is connected to the first control air pressure, and the air core is connected to the second control air pressure, and the first control air pressure and the second control air pressure are independently controlled, wherein the first control air pressure is 5 kPa to 20 kPa higher than the second control air pressure, for example, the first control air pressure is 5 kPa, 15 kPa, or 20 kPa higher than the second control air pressure.
[0084] In practical applications, inert gas is generally introduced into each capillary and the air core surrounded by each capillary to apply controlled gas pressure. The inert gas may be nitrogen, argon, helium, etc.
[0085] In one embodiment of the present application, during the drawing process of the glass mother tube in the aforementioned step S3, the glass mother tube is in an inert gas; during the drawing process of the optical fiber preform in the aforementioned step S5, the optical fiber preform is also in an inert gas.
[0086] Specifically, the drawing process of glass mother tubes and optical fiber preforms is generally carried out in the drawing furnace of the optical fiber drawing tower. Before the drawing process, inert gas is injected into the drawing furnace to ensure that the drawing process is carried out under the protection of the inert gas, which can avoid oxidation reactions of the materials in the furnace and ensure the continuity of optical fiber production.
[0087] Corresponding to the above-mentioned hollow-core anti-resonant optical fiber, the present application also provides an optical fiber cable, comprising at least one hollow-core anti-resonant optical fiber in the above-mentioned embodiment.
[0088] The hollow-core anti-resonant optical fiber, the method for preparing the hollow-core anti-resonant optical fiber and the corresponding beneficial effects provided by the present application are described below in conjunction with specific embodiments.
[0089] Specifically, before designing the fiber structure parameters of the hollow-core antiresonant optical fiber, the inventors of the present application first actually prepared 27As2Te2-39GeSe2-34As2Se3 glass, and used the prepared 27As2Te2-39GeSe2-34As2Se3 glass to test the thermodynamic properties and optical properties of the glass. Subsequently, based on the actual optical properties of the glass, the fiber structure parameters of the hollow-core antiresonant optical fiber were designed, so that the hollow-core antiresonant optical fiber has good optical transmission performance in the 12μm~30μm band. The preparation of 27As2Te2-39GeSe2-34As2Se3 glass and its thermal and optical properties are described below in conjunction with Example 1-1 and Test Examples 1-1 to 1-3:
[0090] Example 1-1
[0091] Step (1): weigh As, Te, Ge and Se with a purity of 99.9999% in a molar ratio of 122:54:39:146, first load Ge and Te into a quartz tube, and evacuate the tube to 9×10 -4 Pa, and then seal the quartz tube.
[0092] Step (2): Place the sealed quartz tube in step (1) into a rocking furnace, heat it to 900°C at a heating rate of 3°C / min, melt it for 5 hours, and obtain an alloy after cooling.
[0093] Step (3): Open the quartz tube seal, add weighed elemental As and elemental Se to the alloy, and then evacuate the quartz tube to 9×10 -4 Pa, and then seal the quartz tube.
[0094] Step (4): Place the sealed quartz tube in step (3) into a rocking furnace, heat it to 800°C at a heating rate of 3°C / min, rock the quartz tube in the rocking furnace to mix the glass liquid evenly, keep the temperature for 10 hours, and obtain 27As2Te2-39GeSe2-34As2Se3 glass after quenching and annealing.
[0095] Test Example 1-1
[0096] Take the 27As2Te2-39GeSe2-34As2Se3 glass prepared based on Example 1-1, grind it into powder, take 10 mg and use differential scanning calorimetry (DSC) to test the heat flow signal released by the glass powder as the temperature rises in the temperature range of 50°C to 400°C. The obtained thermal test curve is as follows: Figure 2 shown. Figure 2 The horizontal axis of the curve is temperature, in °C, and the vertical axis is the heat flux generated by the heat release of the glass plate, in uV / mg.
[0097] The test results show that the glass transition temperature T of 27As2Te2-39GeSe2-34As2Se3 glass g The crystallization temperature of 27As2Te2-39GeSe2-34As2Se3 glass is T x Above 400°C, ∆t (∆t = T x -T g ) above 200°C.
[0098] Combined with the description of steps S1 to S5 above, it can be seen that the preparation of hollow core antiresonant optical fiber involves two drawing processes. Those skilled in the art can understand that the drawing process can only be carried out when the glass is in a molten state. Therefore, the drawing temperature set during the drawing process is related to the glass transition temperature T g Related (drawing temperature is higher than T g ). If the ∆t of the glass material itself is too small, it is easy for the set drawing temperature to be higher than the crystallization temperature of the glass material. The glass material will crystallize during the drawing process, affecting the drawing effect. Figure 2 The test results show that the ∆t of 27As2Te2-39GeSe2-34As2Se3 glass is above 200°C, and it has good thermal stability. Therefore, in the process of using 27As2Te2-39GeSe2-34As2Se3 glass to prepare hollow-core antiresonant optical fiber, this glass material will not show crystallization during the drawing process, and can meet the needs of repeated drawing in the preparation process of hollow-core antiresonant optical fiber.
[0099] Moreover, 27As2Te2-39GeSe2-34As2Se3 glass is superior to the traditional chalcogenide glass Te2As3Se5 glass (T g =135°C) has a higher glass transition temperature. After being prepared into a hollow-core antiresonant fiber, the obtained hollow-core antiresonant fiber can be used at a higher temperature and can be suitable for more application scenarios.
[0100] Test Example 1-2
[0101] The 27As2Te2-39GeSe2-34As2Se3 glass prepared in Example 1-1 was made into a 5 mm thick glass plate. The infrared transmission spectrum of the glass plate in the 3-20 μm band was measured using an infrared Fourier spectrometer. Figure 3 shown. Figure 3 The horizontal axis of the middle curve is wavelength, in μm, and the vertical axis is transmittance.
[0102] The test results show that when the wavelength of the incident light reaches above 18μm, the transmittance of 27As2Te2-39GeSe2-34As2Se3 glass is less than 0.1, that is, 27As2Te2-39GeSe2-34As2Se3 glass has obvious intrinsic absorption for light with a wavelength above 18μm. This application prepares 27As2Te2-39GeSe2-34As2Se3 glass into a hollow-core anti-resonant optical fiber and reasonably designs the optical fiber structural parameters of the hollow-core anti-resonant optical fiber, which can confine the light to the air core for transmission, overcome the influence of the intrinsic absorption of the glass material on the optical fiber transmission loss, and broaden the infrared transmission window of the optical fiber.
[0103] Test Example 1-3
[0104] The 27As2Te2-39GeSe2-34As2Se3 glass prepared in Example 1-1 was made into a 5 mm thick glass plate. The refractive index dispersion curve of the glass plate in the 2-18 μm band was measured using an ellipsometer, as shown in FIG. Figure 4 shown. Figure 4 The horizontal axis of the curve is the wavelength in μm, and the vertical axis is the refractive index.
[0105] The refractive index dispersion characteristics of the 27As2Te2-39GeSe2-34As2Se3 glass obtained from the experiment are specifically used as the basis for designing the fiber structure parameters of the hollow core anti-resonant optical fiber. Specifically, the applicant first gives an alternative scheme for the design of the fiber structure parameters of the hollow core anti-resonant optical fiber, and then imports the designed fiber cross-sectional structure into the Comsol Multiphysics finite element software, uses the wave optics module in the software, selects the material (i.e., 27As2Te2-39GeSe2-34As2Se3 glass), and sets the material properties (such as refractive index) and the fiber structure parameters (such as the number of capillaries, air core diameter, capillary outer diameter, capillary wall thickness, and spacing between capillaries) to calculate the limiting loss of the optical fiber. Then, based on the calculation results, the low-loss transmission window of the corresponding structure optical fiber is obtained, and it is determined whether the low-loss transmission window is within the required 12μm~30μm band, and finally determines the fiber structure that can achieve low-loss transmission for the 12μm~30μm band.
[0106] Based on the above process, the structural parameters of the optical fiber structure determined by the present application that can achieve low-loss transmission for the 12μm~30μm band meet the following requirements: the number of capillaries in the hollow-core antiresonant optical fiber is 8, and the diameter of the air core is between 420μm and 440μm; the outer diameter of the capillary is between 160μm and 180μm; the wall thickness of the capillary is between 13μm and 17μm; and the spacing between the capillaries is between 57μm and 63μm.
[0107] Based on theoretical calculation, the present application calculates the theoretical loss spectrum of the hollow-core antiresonant optical fiber in the following embodiment 2-1:
[0108] Example 2-1
[0109] The structure of hollow core antiresonant fiber can be found in Figure 1 , including an outer tube and 8 capillaries arranged on the inner wall of the outer tube, and its basic optical fiber structural parameters are: the outer diameter of the outer tube is 924μm, the diameter of the air core is 430μm, the outer diameter of the capillary is 170μm, the wall thickness of the capillary is 15μm, and the interval between the capillaries is 60μm.
[0110] The theoretical loss spectrum of the hollow core antiresonant optical fiber provided in Example 2-1 in the 12 μm to 30 μm band is shown in Figure 5 , Figure 5 The horizontal axis of the middle curve is wavelength, in μm, and the vertical axis is transmission loss, in dB / m. The hollow-core antiresonant fiber has three low-loss transmission windows within 12μm~30μm, namely: 13μm~17μm band, 19μm~22μm band, 25μm~29μm band. And the calculation results show that the transmission loss of the hollow-core antiresonant fiber in these three low-loss transmission windows is less than: 2dB / m. It can achieve efficient transmission in the 12μm~30μm far-infrared terahertz critical band.
[0111] Example 2-2
[0112] The basic optical fiber structural parameters are: the outer diameter of the outer tube is 898μm, the diameter of the air core is 420μm, the outer diameter of the capillary is 160μm, the wall thickness of the capillary is 13μm, and the interval between the capillaries is 62μm.
[0113] The theoretical loss spectrum of the hollow core antiresonant optical fiber provided in Example 2-2 in the 12 μm to 30 μm band is shown in Figure 6 , Figure 6The horizontal axis of the middle curve is wavelength, in μm, and the vertical axis is transmission loss, in dB / m. The hollow-core antiresonant fiber has two low-loss transmission windows within 12μm~30μm, namely: 17μm~19μm band, 22μm~26μm band. And the calculation results show that the transmission loss of the hollow-core antiresonant fiber in these two low-loss transmission windows is less than: 2dB / m. It can achieve efficient transmission in the 12μm~30μm far-infrared terahertz critical band.
[0114] Example 2-3
[0115] The basic optical fiber structural parameters are: the outer diameter of the outer tube is 970μm, the diameter of the air core is 440μm, the outer diameter of the capillary is 180μm, the wall thickness of the capillary is 17μm, and the interval between the capillaries is 57μm.
[0116] The theoretical loss spectrum of the hollow core antiresonant optical fiber provided in Example 2-3 in the 12 μm~30 μm band is shown in Figure 7 , Figure 7 The horizontal axis of the middle curve is wavelength, in μm, and the vertical axis is transmission loss, in dB / m. The hollow-core antiresonant fiber has three low-loss transmission windows within 12μm~30μm, namely: 17μm~20μm band, 22μm~25μm band, 28μm~30μm band. And the calculation results show that the transmission loss of the hollow-core antiresonant fiber in these three low-loss transmission windows is less than: 2dB / m. It can achieve efficient transmission in the 12μm~30μm far-infrared terahertz critical band.
[0117] In order to verify the transmission performance of the hollow-core antiresonant optical fiber provided in the present application, the present application also actually prepared the hollow-core antiresonant optical fiber listed in the above-mentioned embodiment 2-1, and tested its transmission loss by experimental means. The preparation process of the hollow-core antiresonant optical fiber is shown in the following embodiment 3-1:
[0118] Example 3-1
[0119] Step (5): Take the 27As2Te2-39GeSe2-34As2Se3 glass prepared in Example 1-1 and prepare a glass mother tube with an outer diameter of 18 mm and an inner diameter of 15 mm.
[0120] Step (6): Use an infrared fiber drawing tower to draw the glass mother tube obtained in step (5) into a capillary tube with an outer diameter of 3.3 mm at a drawing temperature of 320°C.
[0121] Step (7): Take 8 capillaries obtained based on step (6) and a glass mother tube obtained based on step (5), arrange the 8 capillaries in the glass mother tube at equal intervals, and fix the two ends of the capillaries to the glass mother tube with inorganic glue to obtain an optical fiber preform.
[0122] Step (8): Fix the optical fiber preform on the infrared optical fiber drawing tower, connect the air core area formed by the eight capillaries in the optical fiber preform to the first pressure control gas path, keep the pressure at atmospheric pressure, connect the eight capillaries to the second pressure control gas path, the second pressure is 10 KPa higher than the first pressure. Draw the hollow core anti-resonant optical fiber according to the optical fiber structural parameters defined in Example 2-1, the drawing temperature is 320°C, and finally obtain the hollow core anti-resonant optical fiber having the structure in Example 2-1.
[0123] The end face micrograph of the hollow core antiresonant optical fiber finally prepared based on the above steps (5) to (8) is as follows: Figure 8 shown.
[0124] Test Example 3-1
[0125] Take the hollow-core antiresonant optical fiber prepared in Example 3-1, transmit light with a wavelength in the range of 15 μm to 22 μm through the hollow-core antiresonant optical fiber, and measure the transmission loss of the hollow-core antiresonant optical fiber. The test loss spectrum obtained is as follows: Fig. 9 The measurement results show that the actual transmission baseline loss of the hollow-core antiresonant fiber in the 19μm~22μm band is about 10dB / m, and it can achieve low-loss transmission in the 12μm~30μm band.
[0126] In addition, the applicant also measured the transmission loss of the hollow-core anti-resonant optical fiber having the structure in Example 2-2 to Example 2-3 based on the same test method as in Experimental Example 3-1. The measurement results all proved that the corresponding hollow-core anti-resonant optical fiber can achieve low-loss transmission in the 12μm~30μm band.
[0127] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0128] The above description is only a preferred embodiment of the present application and is not intended to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application are included in the protection scope of the present application.
Claims
1. A hollow core antiresonant optical fiber, characterized in that: include: External pipe; A plurality of capillaries are arranged on the inner wall of the outer tube at equal intervals along the extension direction of the outer tube; An air core, formed by being surrounded by the plurality of capillaries; Wherein, the material of the outer tube and the capillary is 27As2Te2-39GeSe2-34As2Se3 glass.
2. The hollow core antiresonant optical fiber according to claim 1, characterized in that: The number of the capillaries is 8, the diameter of the air core is between 420 μm and 440 μm, the outer diameter of the capillary is between 160 μm and 180 μm, the wall thickness of the capillary is between 13 μm and 17 μm, and the interval between the capillaries is between 57 μm and 63 μm; The diameter of the air core is the diameter of the inscribed circle formed by the capillaries, and the interval between the capillaries is the minimum distance between adjacent capillaries.
3. The hollow core antiresonant optical fiber according to claim 1 or 2, characterized in that: The hollow core anti-resonance optical fiber has a low-loss transmission window with a theoretical transmission loss lower than 2dB / m in the 12μm-30μm waveband.
4. A method for preparing a hollow core antiresonant optical fiber, characterized in that: include: Elemental As, elemental Te, elemental Ge and elemental Se were weighed in a molar ratio of 122:54:39:146, and 27As2Te2-39GeSe2-34As2Se3 glass was prepared by melting and annealing. Prepare a glass mother tube using the 27As2Te2-39GeSe2-34As2Se3 glass; Performing wire drawing on the glass mother tube to obtain a capillary tube; Inserting a plurality of the capillaries into a glass mother tube, and arranging the inserted capillaries at equal intervals on the inner wall of the glass mother tube to obtain an optical fiber preform; The optical fiber preform is subjected to a drawing process to obtain a hollow-core anti-resonant optical fiber.
5. The method according to claim 4, characterized in that The process of preparing 27As2Te2-39GeSe2-34As2Se3 glass by melting and annealing includes: Adding the single substance Ge and the single substance Te into a melting container, placing the melting container into a melting furnace, melting the single substance Ge and the single substance Te, and obtaining an alloy after cooling; The single element As and the single element Se are added into the melting container, and the melting container is placed into a melting furnace to melt the alloy, the single element As and the single element Se, and the molten glass obtained by the melting is quenched and then annealed to obtain 27As2Te2-39GeSe2-34As2Se3 glass.
6. The method according to claim 5, characterized in that When the single substance Ge and the single substance Te are melted, the melting temperature is between 850°C and 900°C, and the melting time is between 5 hours and 10 hours; when the alloy, the single substance As and the single substance Se are melted, the melting temperature is between 750°C and 800°C, and the melting time is more than 10 hours.
7. The method according to claim 4, characterized in that The number of capillaries inserted into the glass mother tube is 8, and in the hollow-core antiresonant optical fiber, the diameter of the air core is between 420 μm and 440 μm, the outer diameter of the capillary is between 160 μm and 180 μm, the wall thickness of the capillary is between 13 μm and 17 μm, and the spacing between the capillaries is between 57 μm and 63 μm; wherein the diameter of the air core is the diameter of the inscribed circle formed by each of the capillaries, and the spacing between the capillaries is the minimum distance between adjacent capillaries.
8. The method according to claim 4, characterized in that During the drawing process of the optical fiber preform, each capillary in the optical fiber preform is connected to a first controlled air pressure, and the air core formed by the capillaries is connected to a second controlled air pressure, and the first controlled air pressure is 5 kPa to 20 kPa higher than the second controlled air pressure.
9. The method according to claim 4, characterized in that During the process of drawing the glass mother tube, the glass mother tube is in an inert gas; during the process of drawing the optical fiber preform rod, the optical fiber preform rod is in an inert gas.
10. An optical fiber cable, characterized in that: The hollow-core antiresonant optical fiber comprises at least one hollow-core antiresonant optical fiber according to any one of claims 1 to 3.
Citation Information
Patent Citations
Flexible high-resolution infrared chalcogenide glass optical fiber image transmission bundle and manufacturing method
CN104181636A
Manufacturing device and method of chalcogenide fiber grating
CN105334567A